Efecto de la privación de sueño MOR sobre la expresión de moléculas reguladoreas del metabolismo y citocinas en ratas - Brianza Padilla, Malinalli (Universidad Autónoma Metropolitana, 2016)
Sleep is an indispensable physiological activity, it is considered that the human being spends a third of his life sleeping, which indicates that the functions of sleep are of vital importance. Although the function of sleep is not fully described, several theories are considered, among them, it deters the regulation of metabolism and the immune response. It has been observed that sleep deprivation induces important alterations in glucose metabolism, and believes that there is a relation between obesity and lack of sleep, besides it has been shown that sleep deprivation induces alterations in the immune response , this alterations also are related with some alterations as the insulin resistance, however little has been described about the response of the organism to different periods of sleep deprivation and its recovery, therefore the effect of the MOR sleep deprivation was evaluated in different periods (1 day, 4 days and 8 days) and 20 days of recovery after 8 days of MOR sleep deprivation, on the concentration and expression of metabolic regulatory molecules and cytokines in rats, the first day it´s found a decrease of concentration of leptin, insulin, IL-10 and IL-1β and increase the miRNAs 155, 146a and 223 as well as the concentration of IL-6. At day 4, the increase in food consumption, in the expression of mRNA resistine, TNF, ACSL1 and PPARγ in liver were observed. It decreases leptin, expression of GLUT4 and miRNA 223. On day 8 of MOR sleep deprivation, the increase in food consumption is maintained, ghrelin, corticosterone, IL-10, IL-6 and Leptin, insulin and miRNAs 16 and 126. Passing the recovery period the expression of adiponectin increases, FATP, ACSL 1, PPARγ, IL-6, as well as TNF and IL-6 concentration and decreased expression of GLUT4 and the concentration of IL-10. The results demonstrate that the response of the organism subjected to the different periods of MOR sleep deprivation, the increase in food consumption is maintained, ghrelin, corticosterone, IL-10, IL-6 and Leptin, insulin and miRNAs 16 and 126. Passing the recovery period the expression of adiponectin increases, FATP, ACSL 1, PPARγ, IL-6, as well as TNF and IL-6 concentration and decreased expression of GLUT4 and the concentration of IL-10. The results demonstrate that the response of the organism subjected to the different periods of MOR sleep deprivation depends on time of the same and that a prolonged recovery time is insufficient to reverse the alterations caused by MOR sleep deprivation.; El sueño es una actividad fisiológica indispensable, se considera que el ser humano pasa una tercera parte de su vida durmiendo, lo que indica que las funciones del sueño son de vital relevancia. A pesar de que la función del sueño no está descrita en su totalidad se consideran varias teorías, entre ellas destaca la regulación del metabolismo y de la respuesta inmune. Se ha observado que la privación de sueño induce importantes alteraciones en el metabolismo de la glucosa, y se cree que existe una relación entre la obesidad y la falta de sueño, además de ello se ha demostrado que la privación de sueño induce alteraciones en la respuesta inmune. Dichas alteraciones también se relación con algunas alteraciones como la resitencia a la insulina, sin embargo poco se ha descrito sobre la respuesta del organismo ante diferentes periodos de privación de sueño y su recuperación. Por lo anterior se evaluó el efecto de la privación de sueño MOR a diferentes periodos (1 día, 4 días y 8 días) y 20 días de recuperación posterior a 8 días de privación de sueño MOR, sobre la concentración y expresión de moléculas reguladoras del metabolismo y citocinas en ratas, al primer día se encuentra una disminución en la concentración de leptina, insulina, IL-10 e IL-1β e incrementan los miRNAs 155, 146a y 223 así como la concentración de IL-6. Al día 4 se observa incremento en el consumo de alimento, en la expresión del RNAm de resistina, TNF, ACSL1 y PPARγ en hígado. Así mismo disminuye la leptina, la expresión de GLUT4 y el miRNA 223. En el día 8 de privación de sueño MOR se mantiene el aumento en el consumo de alimento, se incrementa la grelina, la corticosterone, IL-10, IL-6 y diminuyen la leptina, insulina y los miRNAs 16 y 126. Pasando el periodo de recuperación se incrementa la expresión de adiponectina, FATP, ACSL 1, PPARγ, IL-6, así como la concentración de TNF e IL-6 y disminuye la expresión de GLUT4 y la concentración eño MOR es dependiente al tiempo de la misma y que es insuficiente un periodo prolongado de recuperación para revertir las alteraciones provocadas por la privación de sueño MOR.